Assembled Ag-doped α-MnO2@δ-MnO2 nanocomposites with minimum lattice mismatch for broadband microwave absorption. (15th October 2020) - Song, Lulu; Duan, Yuping; Liu, Jia; Pang, Huifang
Abstract: Building core@shell nanostructures and doping ions are two important strategies to optimize the performance for the microwave impedance matching and attenuation. In this research, the Ag-doped α-MnO2 @δ-MnO2 was successfully synthesized by combining hydrothermal reaction and chemical deposition reaction. Driven by the lowest surface energy principle, all the δ-MnO2 nanosheets nucleate on the surface of α-MnO2 nanowires. During this process, the edge of nanosheets attach on the α-MnO2 nanowire with low lattice mismatch of δ (201)//α (211) (nearly 0) and vertically grow on the nanowires surfaces, then the assembled core-shell composites can be prepared. The core-shell composites exhibit synergistic effect and improved the impedance matching, so that the absorbing performance has been obtained. The composite shows the minimum reflection loss (RL) of −53.67 dB at 13.28 GHz for 1.8 mm thickness, and the broadest effective absorbing bandwidth (RL < −10 dB) is 5.44 GHz as the thickness was 1.9 mm. The excellent performance is come from the preferable impedance matching, the large heterogeneous existence of the interfaces and the numerous transmission paths for microwave. Graphical abstract: Image 1